2003
DOI: 10.1046/j.1525-1470.2003.20318.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Recalcitrant Warts in Children Using Intralesional Mumps or Candida Antigens

Abstract: Intralesional injection of mumps and Candida skin test antigens has been shown to be effective in the treatment of warts. Warts are generally difficult to treat in children. To determine the efficacy of intralesional skin test antigen injection for the treatment of resistant warts in children, we treated 47 pediatric patients with one or more warts with intralesional injection of mumps or Candida skin test antigen into one wart. Twenty-two patients (47%) with resistant warts experienced complete resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
146
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(168 citation statements)
references
References 8 publications
15
146
6
1
Order By: Relevance
“…The therapeutic response to intralesional MMR vaccine in our study was much higher than that reported by Kus et al 17 (29.4%), Clifton et al 18 (47%), King et al 19 (50%), Signore 20 (51%) and Horn et al 21 (53%), slightly higher than that reported by Johnson and Horn 22 (70.9%), similar to that reported by Phillips et al 23 (72%) and slightly lower than that reported by Johnson et al 24 (74%) , Brunk 25 (85%), Gupta et al 26 (88.9%) and Maronn et al 27 (87%). The presence of three synergistic viral antigens in MMR vaccine that could be associated with higher stimulation of the immune system may explain the relatively higher response in our study as compared to most of the related studies which utilize either a single antigen [17][18][19][20][21][22][23][24] or a combination of antigens. 19,22 The exact mechanism of action of intralesional immunotherapy is still obscure.…”
Section: Discussioncontrasting
confidence: 74%
“…The therapeutic response to intralesional MMR vaccine in our study was much higher than that reported by Kus et al 17 (29.4%), Clifton et al 18 (47%), King et al 19 (50%), Signore 20 (51%) and Horn et al 21 (53%), slightly higher than that reported by Johnson and Horn 22 (70.9%), similar to that reported by Phillips et al 23 (72%) and slightly lower than that reported by Johnson et al 24 (74%) , Brunk 25 (85%), Gupta et al 26 (88.9%) and Maronn et al 27 (87%). The presence of three synergistic viral antigens in MMR vaccine that could be associated with higher stimulation of the immune system may explain the relatively higher response in our study as compared to most of the related studies which utilize either a single antigen [17][18][19][20][21][22][23][24] or a combination of antigens. 19,22 The exact mechanism of action of intralesional immunotherapy is still obscure.…”
Section: Discussioncontrasting
confidence: 74%
“…22,23 Nongenital warts occur in 7% to 10% of the general population, with the incidence peaking between the ages of 12 and 16 years. 44 Viral warts occur equally in both sexes in children ages 2 to 12 years and are among the three most common dermatoses treated. 31,45,46 Approximately 23% of warts regress spontaneously within 2 months, 30% within 3 months and 65% to 78% within 2 years.…”
Section: Etiologymentioning
confidence: 99%
“…The idea of using Candida skin testing reagent as a novel vaccine adjuvant came about from observations that intralesional injections of recall antigens result in common wart regression (48)(49)(50)(51)(52)(53)(54). Traditionally, recall antigens, which typically include a panel derived from Candida, mumps virus, and Trichophyton, were used as a control to indicate intact cell-mediated immunity in patients (48)(49)(50)(51)(52)54).…”
Section: De Novo Immune Stimulationmentioning
confidence: 99%
“…Traditionally, recall antigens, which typically include a panel derived from Candida, mumps virus, and Trichophyton, were used as a control to indicate intact cell-mediated immunity in patients (48)(49)(50)(51)(52)54). These studies suggested that T cells may have a role in wart regression.…”
Section: De Novo Immune Stimulationmentioning
confidence: 99%